2019
DOI: 10.1002/ps.5628
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of new mutations in mitochondrial cytochrome b that confer resistance to bifenazate and acequinocyl in the spider miteTetranychus urticae

Abstract: BACKGROUND In spider mites, mutations in the mitochondrial cytochrome b Qo pocket have been reported to confer resistance to the Qo inhibitors bifenazate and acequinocyl. In this study, we surveyed populations of the two‐spotted spider mite Tetranychus urticae for mutations in cytochrome b, linked newly discovered mutations with resistance and assessed potential pleiotropic fitness costs. RESULTS We identified two novel mutations in the Qo site: G132A (equivalent to G143A in fungi resistant to strobilurins) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 62 publications
3
50
1
Order By: Relevance
“…However, the fast development of resistance in the species, in part due to biological characteristics such as a short life cycle, high reproductive potential, arrhenotokous reproduction, together with a broad host plant range, reduces the efficacy of the application of acaricides (Dermauw et al 2013;Van Leeuwen et al 2010;Wybouw et al 2019). It is therefore important to continue to develop acaricides with new modes of action and limited cross-resistance to other commercially available compounds to secure proper resistance management in T. urticae (Nauen et al 2012;Van Leeuwen, Thomas et al 2015;Fotoukkiaii et al 2019). The carboxanilide pyflubumide is a recently developed acaricide by Nihon Nohyaku Co. Ltd with excellent activity against phytophagous mites of the genus Tetranychus and Panonychus (both belong to the Tetranychidae family) .…”
Section: Introductionmentioning
confidence: 99%
“…However, the fast development of resistance in the species, in part due to biological characteristics such as a short life cycle, high reproductive potential, arrhenotokous reproduction, together with a broad host plant range, reduces the efficacy of the application of acaricides (Dermauw et al 2013;Van Leeuwen et al 2010;Wybouw et al 2019). It is therefore important to continue to develop acaricides with new modes of action and limited cross-resistance to other commercially available compounds to secure proper resistance management in T. urticae (Nauen et al 2012;Van Leeuwen, Thomas et al 2015;Fotoukkiaii et al 2019). The carboxanilide pyflubumide is a recently developed acaricide by Nihon Nohyaku Co. Ltd with excellent activity against phytophagous mites of the genus Tetranychus and Panonychus (both belong to the Tetranychidae family) .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported T. urticae strains with high levels of resistance against certain active ingredients, 22–25 including some cases of cross‐ or multiple resistance 18,26–28 . Several mechanisms have been associated with these phenotypes, with the most studied being target‐site mutations, 9,27,29–32 and over‐expression of detoxification enzymes 33–39 …”
Section: Introductionmentioning
confidence: 99%
“…L1024V, A1215D, and F1538I mutations of voltage-gated chloride channel genes and a I1017F mutation of chitin synthase I have been reported [30,31]. Van Leeuwen et al [32] reported G126S, I136T, S141T, P262T and A133T, G132A [18] mutations in cytb of acequinocyl-and bifenazate-resistant T. urticae. In addition, I256V and N321S mutations were reported in cytb of acequinocyl-resistant T. urticae in a recent study [19].…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods have developed two main mechanisms of acaricide resistance: decreasing exposure due to quantitative or qualitative changes in major detoxification enzymes and decreasing sensitivity due to changes in target-site sensitivity caused by point mutations [15][16][17]. Fotoukkiaii et al [18] demonstrated that amino acid residue substitutions (G126S + A133T) in cytochrome b of T. urticae are associated with acequinocyl resistance. Kim et al [19] also observed the I256V + N321S point mutations in an acequinocyl-resistant strain.…”
Section: Introductionmentioning
confidence: 99%